Analysis of The Influence of Situational Digital Advertising Through Online Video Sharing and Social Media Platform on Customers Intention to Purchase at E-Commerce Application Shopee - Ekaresty Haes, Putri; Dharmawan, Donny; Serius Nazara, Desman; Arwani, Mokhamad; Yuniarti Utami, Eva (SEULANGA SYSTEM PUBLISHER, 2023)
This research aims to determine the effect of advertising exposure on shopping interest. The paradigm used in this research is the positivism paradigm. This study uses a quantitative approach. This research uses non-experimental research methods with a type of method, namely the survey method. The population in this study were students. The number of samples in this research was 100. The primary data for this research uses data obtained from a questionnaire that has been distributed in the form of a Google Form. The linear regression test in this research uses product moments with SPSS version 24 for Windows. Based on the findings and discussion of the research that has been carried out, it can be concluded that the level of advertising exposure is in the medium category with a percentage of 60%. The level of interest in shopping through applications is also in the medium category, with a percentage of 40%. From the research results, it can be concluded that advertising exposure influences shopping interest. Based on the results of the t-value, namely 3.5 > 1.98, The coefficient of determination in this equation has a positive value of 12.5%. This figure means that the advertising exposure variable does not have a big influence on shopping interest at 12.5%. Other factors that were not considered in this study contributed the remaining 87.5%. So the conclusion is that if the advertising exposure variable increases, then interest in shopping through the application will also increase. Vice versa, if advertising exposure decreases, shopping interest also decreases.